Comparative efficacy of combined oral contraceptive capsules and vitamin D–combined oral contraceptive capsules on ovulatory dysfunction: A randomized clinical trial - mahdis chegini; khadije hajizade; azize farshbaf; fateme lalooha; Mahnaz Shahnazi (Journal of Research Development in Nursing and Midwifery, 2023)
Background: Food intake and metabolism might play central roles in causing and treating menstrual disorders. Vitamin D may lead to the improvement of folliculogenesis through anti-Mullerian hormone (AMH). This study aimed to compare the effect of vitamin D intake with that of the combined oral contraceptive (COC) capsules on ovulatory dysfunction. Methods: This study was conducted on 60 eligible women referred to Kowsar Qazvin Hospital with a complaint of abnormal uterine bleeding (AUB). They had a history of excessive, long, and irregular bleeding. The participants in the control and intervention groups received 1 oral LD capsule and a combination of vitamin D and LD capsules on a daily basis for 3 months, respectively. The menstrual bleeding volume, the number of menstrual days, and the menstrual cycle length were evaluated before, during, and after the intervention. The Mann-Whitney U test, Friedman test, independent t test, and Cochran Q test were used in SPSS version 24 for data analysis. P values less than 0.05 were considered statistically significant. Results: The menstrual bleeding intensity decreased significantly in the intervention group (vitamin D–LD capsule; P = 0.001). Over time, both intervention and control groups showed a significant improvement in the number of menstrual days and menstrual cycle length, resulting in a more normal menstrual cycle. However, these 2 parameters remained more natural in the intervention group, a finding which did not indicate any significant differences. Conclusion: Vitamin D can be used along with LD capsules as a supplementary treatment to lessen menstrual bleeding intensity.